Geomechanical stability of CO2 containment at the South West Hub Western Australia: A coupled geomechanical–fluid flow modelling approach. (June 2015) - Zhang, Y.; Langhi, L.; Schaubs, P.M.; Piane, C. Delle; Dewhurst, D.N.; Stalker, L.; Michael, K.
Highlights: We model geomechanical stability during CO2 injection at the South West Hub Western Australia. Five single-phase fluid injection rates of 1–5 million tonnes per year are simulated. These injection scenarios would not lead to the reactivation of faults. Models predict small average ground surface uplifts in the range of 0.4–1.8 cm over 20 years. Abstract: An area in the Southern Perth Basin has been selected as a potentially suitable site for CO2 injection and storage as a part of the South West Hub Project (SW Hub), due to its proximity to major CO2 emission sources and the presence of potentially suitable geology. This 3D modelling study attempts to assess the geomechanical stability of faults and intact host rocks during CO2 injection at the SW Hub. The stratigraphy and fault structure of the 3D model are based on the architecture of an E–W cross section in a pre-existing 3D geological model that represents a comprehensive synthesis of seismic, stratigraphic and structural data. In the models, the rocks and faults are simulated as Mohr–Coulomb elastic–plastic materials, and their geomechanical and hydrological properties are based on experimental data from the Harvey-1 drill core samples and also information from literature. A series of models are performed to assess five injection scenarios with injection rates of 1–5 million tonnes per year over a period of 20 years. The results show that the simulated CO2 injection scenarios would not lead to fault reactivation or breach the overlying Yalgorup or Eneabba Shale formations in the area. Some small smooth uplifts are recorded as a result of injection. In the models assuming weak faults, average ground surface uplifts are 0.4–1.8 cm for the injection rates of 1–5 million tonnes per year, over an area of approximately 2.5 km radius around the hypothetical injection site. Uplifts are marginally smaller when assuming strong faults.